solve for (x) in this equation (3x^2)/(x^2-1)=(4x)/(x-1)

Notice: Undefined variable: position6 in /home/domains2/public_html/painphr.com/show.php on line 143

Guide :

solve for (x) in this equation (3x^2)/(x^2-1)=(4x)/(x-1)

This looks like a quadratic equation, but the result are -2/3 and 2 which I dont know how to solve it.

Research, Knowledge and Information :

Notice: Undefined variable: go_page in /home/domains2/public_html/painphr.com/show.php on line 211

x^2-1=0 - Equation Calculator - Symbolab

Equation Calculator Solve linear, ... 5x-6=3x-8; x^2-x-6=0; x^4-5x^2+4=0 \sqrt ... A quadratic equation is a second degree polynomial having the general form ax^2 ...

How to solve for x in the equation [math]2x^2-1 = 2(x-1)^2 ...

... can also be written as [math]2x^2 - 4x + 2 + 4x -3 = 2 (x - 1)^2 + 4x - 3 ... I solve for x in the equation [math]2x^2-1 = 2 ... I solve the equation [math]x^3-3x+1=0

How to solve |2x+1| < |x+2| - Quora

How do I solve for x in the equation [math]2x^2-1 = 2 ... 4x^2+4x+1 < x^2+4x+4 3x^2 < 3 x^2< 1 Here, x can be positive or negative both. So out solution will be:

Solve For X: 4x^2+2x+2 = 0 - coolconversion.com

... Solve For X: 4x^2+2x+2 = 0 . Or how to solve the quadratic equation where ... to solve a equation like ax² ... Solve 4x^2-17x-3 = 0; Solve 3x^2+16x+1 = 0; Solve ...

How do you solve 4x - 2( x - 4) = - 2+ 5x - 2? | Socratic

x=4. 4x-2(x-4)=-2+5x-2 is the problem. To solve it, ... out the -4 on the right side of the equation, giving us 8+4=3x-4 ... How do you solve #int x^-4*sqrt(x^4+1) ...

How do you solve x/2 + x/3 - 1 = x/6 + 3? | Socratic

Now we move all of the fractions to one side of the equation and the whole numbers to the other: # ... How do you solve #4x ^ { 2} ... HOW do you solve #(x^2-1)/ (2 ...

SOLUTIONS TO IMPLICIT DIFFERENTIATION PROBLEMS

SOLUTIONS TO IMPLICIT DIFFERENTIATION PROBLEMS ... (Equation 2) x 2 + y 2 = 1 ... (Now solve for y' .) 4x (x 2 +y 2) + 4y(x 2 +y 2) ...

Mathway | Solve for x 2/(x+2)+1/5=6/(x+5)

Solve for x 2/(x+2)+1/5=6/(x+5) ... move it to the right side of the equation by subtracting from both sides. ... [x 2 1 2 π ∫ ⁡ x d x ...

3x+1=4x-2 - Get Easy Solution

Simple and best practice solution for 3x+1=4x-2 equation ... If it's not what You are looking for type in the equation solver your own equation and let us solve it ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

how can i solve these equations?

how can i solve these equations? x + 3y – z = 2 x – 2y + 3z = 7 x + 2y – 5z = –21 We eliminate one of the unknowns (x, y or z, take your choice), leaving two unknowns. Then, we eliminate a second one, giving us an equation with only one of the unknowns. Solve for that and plug that value in

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

a sistem equation

a sistem equation 3x-5y-2z=-5 6x+2y+3z=5 4x-3y-z=8 x=? ;y=? ; z=? 1) 3x - 5y - 2z = -5 2) 6x + 2y + 3z = 5 3) 4x - 3y - z = 8 The way to solve systems like this is to sequentially eliminate each unknown so that there is only one left. That lets you solve for the value of that remaining unknown, an

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

Solve {3x-2y+2z=30, -x+3y-4z=-33, 2x-4y+3z=42}

Solve {3x-2y+2z=30, -x+3y-4z=-33, 2x-4y+3z=42} Please just solve the set provided above!!!! This will be a bit more involved than the systems with two unknowns, but the process is the same. The plan of attack is to use equations one and two to eliminate z. That will leave an equation with x and y.

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

2x+y=9 x-2z=-3 2y+3z=15

2x+y=9 x-2z=-3 2y+3z=15 Forgot how to do This. Problems Solving systems of this type requires eliminating all but one unknown so you can solve for that unknown. Then, plug that value into one of the equations to solve for another of the unknowns. Finally, plug both of those values into an equation

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

x - z = -3, y + z = 9, -2x + 3y +5z = 33

Problem: x - z = -3, y + z = 9, -2x + 3y +5z = 33 1) x - z = -3 2) y + z = 9 3) -2x + 3y + 5z = 33 Add equation 2 to equation 1.      x     - z = -3 +(    y + z =  9) ------------------   x + y     = 6 4)

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

x+2y+3z=14,x-y+2z =5, 2x + 2y +z= 11

x+2y+3z=14,x-y+2z =5, 2x + 2y +z= 11 1) x + 2y + 3z = 14 2) x - y + 2z = 5 3) 2x + 2y + z = 11 When there are three variables, it is easier to solve by elimination, but apparently this is to be solved by substitution. I'll number the equations as I go along, so you can see where I get

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

3x + 6y – 6z = 9 2x – 5y + 4z = 6 -x +16y + 14z = -3 what is the answer

3x + 6y – 6z = 9 2x – 5y + 4z = 6 -x +16y + 14z = -3 what is the answer how do you solve it and what are the answers ? 1)  3x + 6y – 6z = 9 2)  2x – 5y + 4z = 6 3)  -x +16y + 14z = -3 The first objective is to eliminate z so we can solve for x and y. It's a multi-step proces

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

solve following system of equations

Problem: solve following system of equations solve the following system of equations: x-2y+z=6 , 2x+y-3z=-3, x-3y+3z=10 1) x - 2y + z = 6 2) 2x + y - 3z = -3 3) x - 3y + 3z = 10 Multiply equation 1 by 3. 3(x - 2y + z) = 6 * 3 4) 3x - 6y + 3z = 18 Add equation 2 to equation 4. &nbs

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

using the elimination method solve 6=6x+6y and -14y=18x+14

using the elimination method solve 6=6x+6y and -14y=18x+14 help me solve step by step 1) 6 = 6x + 6y 2) -14y = 18x + 14 Re-write equation 1: 3) 6x + 6y = 6 It is standard to have the unknowns of the left side of the equation. Now, for equation 2. -14y = 18x + 14 4) -18x - 14y = 14

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

solve three way equation with z. 1:3x-2y+2z=30 2:-x+3y-4z=-33 3:2x-4y+3z=42

Solve {3x-2y+2z=30, -x+3y-4z=-33, 2x-4y+3z=42} Please just solve the set provided above!!!! 1)  3x-2y+2z=30 2)  -x+3y-4z=-33 3)  2x-4y+3z=42 Equation one; multiply by 2 so the z term has 4 as the coefficient. 3x - 2y + 2z = 30 2 * (3x - 2y + 2z) = 30 * 2 4)  6x - 4y + 4z = 60 A